PENYUSUNAN ANALISIS JABATAN OLEH BAGIAN ORGANISASI SEKRETARIAT DAERAH PEMERINTAH KOTA MAGELANG - Ardhia Regina Pramesti; Hanung Eka Atmaja (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2021)
This study aims to describe the Compilation of Job Analysis in Pemerintahan Kota Magelang. This study uses a qualitative method with data collection techniques in the form of interviews and observations. The informant determination technique used by the writer is purposive sampling. Section chairman, Chairperson of Subdivision and staff Staff at the Organization Section of the Secretariat of the Dearah are informants in this study. The results of the study aimed at compiling a job analysis on the part of the organization running effectively by combining several methods, such as the method of checking documents, interviews and observing the field of employees. Managing employees who are spread out in the regional apparatus in the government system needs to place the right human resources as the main asset for the institution. As a government agency, it is necessary to prepare a job analysis which is part of the management of human resources in the organization as a determination of the content of a position that includes duties, responsibilities, authority, working conditions, education, expertise, ability, work experience, and relationships with other positions in the organization, as well as the occupational requirements needed by an employee to be able to carry out work duties in the position he is carrying well.